Adaptive backstepping control of uncertain systems with actuator failures and subsystem interactions - Wang, Wei (2011)
In this thesis, new methodologies of designing adaptive controllers for uncertain systems in the presence of actuator failures and subsystem interactions are investigated. Compared to currently available results on the related research, we have made progress in improving transient performance of the system in failure cases, relaxing assumptions including finite number of failures and matching condition, stabilizing large scale systems with interactions depending on subsystem inputs. These results are of great significance for control problems of many practical systems, such as aircrafts, spacecrafts, powever systems.